A system approach to enable digital beamforming with direct radiating arrays: The joint use of precoding and sparse arrays. (1st June 2021) - Vidal, Florian; Legay, Hervé; Goussetis, George; Segneri, Andrea
Summary: Digital beamforming with an active array antenna has become, these past years, the holy grail for flexible satellite payloads. This architecture enables a power, frequency and beam steering flexibility that meets the requirements of a wide range of user terminal distributions. Matching these distributions may be challenging, especially if user terminals are co‐located. In this case, narrower beams are needed to utilise high‐frequency reuse factors while avoiding inter‐beam interference. Small beamwidths, however, require large antenna diameters, which implies for conventional antenna arrays many radiating elements and subsequently an increased complexity. A way to reduce the number of radiating elements is to resort to sparse arrays with an irregular layout of radiating elements. A disadvantage of this type of antenna is their high side lobe levels when scanning the beams. A robust on‐board precoding strategy based on the knowledge of the users' positions and the antenna gain over the coverage is proposed to mitigate the interference arising from high side lobe levels. A circular direct radiating array and a sparse direct radiating array based on a sunflower design are compared with respect to the capacities they can achieve, and the complexity of the processor required to perform full digital beamforming. Abstract : Digital beamforming with an active array antenna has become, these past years, the holy grail for flexible satellite payloads. This architecture enables a power, frequency and beam steering flexibility that meets the requirements of a wide range of user terminal distributions. A robust on‐board precoding strategy based on the knowledge of the users' positions and the antenna gain over the coverage is proposed to mitigate the interference arising from high side lobe levels.